2020
DOI: 10.1680/jgeot.18.p.053
|View full text |Cite
|
Sign up to set email alerts
|

Saturation and its effect on the resilient modulus of a pavement formation material

Abstract: This paper reports the effects of changing degree of saturation on the stiffness of a typical railway formation material. Material dynamically compacted to a target dry density over a range of water contents was cyclically loaded in triaxial and hollow cylinder apparatus. The results of both test types show the large effect of the degree of saturation on stiffness. In both the cyclic triaxial apparatus and the equivalent stress path in the cyclic hollow cylinder apparatus, the resilient modulus (MR) increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The clay fraction of the tested soil is Hymod Prima [12], plastic Ball Clay consisting of disordered kaolinite, micaceous material, and quartz. The same soil has commonly been used in research studies, see for example Gra ¨be & Clayton [12], Mamou et al [23] and Blackmore et al [7]. The specimens were compacted in a compaction mould with a height of 200 mm and a diameter of 100 mm using a drop hammer following the standard Proctor test procedure [5].…”
Section: Testing Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The clay fraction of the tested soil is Hymod Prima [12], plastic Ball Clay consisting of disordered kaolinite, micaceous material, and quartz. The same soil has commonly been used in research studies, see for example Gra ¨be & Clayton [12], Mamou et al [23] and Blackmore et al [7]. The specimens were compacted in a compaction mould with a height of 200 mm and a diameter of 100 mm using a drop hammer following the standard Proctor test procedure [5].…”
Section: Testing Methodologymentioning
confidence: 99%
“…Experimental results of cyclic testing showed that the response of unsaturated soils is dependent on soil water retention properties while information on both suction and water saturation levels are required to evaluate the accumulated permanent deformation and resilient modulus (e.g. [7,14,21,28,46]). Therefore, any interpretive framework developed for the cyclic response of unsaturated soils requires a water retention counterpart that recognises the evolution of soil suction and water saturation under cyclic loading conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, seasonal variations in the degree of saturation are expected during the life of the pavement, since it goes through fluctuations in the water table level, water percolation, infiltration by surface cracks, lateral movements through the shoulder, among others [1]. The occurrence of excessive humidity produces a reduction in the pavement's support capacity, starting its degradation ( [2], [3], [4], [5]).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies suggest that the effects of principal stress rotation on the resilient stiffness of unsaturated sand / clay materials may be secondary (Blackmore et al 2019), but in saturated conditions, principal stress rotation may be significant (Xiao et al 2013;Cai et al 2015Cai et al , 2016Qian et al 2016;Guo et al 2017). Principal stress rotation affects both the axial strain and the resilient stiffness of sand clay mixes dominated by the sand fraction (Gräbe andClayton 2009, 2014).…”
Section: Introductionmentioning
confidence: 99%